A method for preparing manganese monoxide hollow nanosphere zinc-telluride battery positive electrode material
By synthesizing manganese monoxide hollow nanospheres @nitrogen-doped carbon nanosheet heterostructures in the positive electrode material of the aqueous zinc tellurium battery, the problem of poor reaction kinetics of the aqueous zinc tellurium battery is solved, and the electrochemistry is significantly improved performance.
Patent Information
- Application Number
- CN202311812835.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-27
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-12-27
AI Technical Summary
The existing aqueous zinc tellurium batteries have a low ion/charge migration rate due to the large atomic radius of tellurium element and poor solid reaction kinetics, which limits the improvement of electrochemical performance.
Nitrogen-doped carbon nanosheets are generated by pyrolysis of melamine, and mixed with manganese acetate tetrahydrate for two-step pyrolysis reaction to synthesize manganese monoxide hollow nanospheres, and finally load the tellurium species to form tellurium/manganese monoxide hollow nanospheres @Na-doped carbon nanosheet heterostructure positive electrode material.
This structure can load more tellurium species, improve the utilization rate of tellurium species, enhance the permeability of the electrolyte and expose more active sites, promote the kinetics of redox reactions, reduce the reaction energy barrier, and significantly improve the electrochemical performance of water-based zinc tellurium tellurium cells .
Smart Images

Figure CN117776265B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of energy storage material preparation, and specifically relates to a method for preparing a zinc-tellurium battery positive electrode material by loading a manganese monoxide hollow nanosphere @ nitrogen-doped carbon nanosheet heterostructure with tellurium species. Background Art
[0002] Tellurium has a high capacity (420 mAh g –1 ), high conductivity (2×10 2 S m –1 ), abundant storage resources and low cost have made aqueous zinc-telluride batteries a research hotspot in the field of energy storage.
[0003] However, the atomic radius of tellurium is relatively large, which will reduce the ion / charge migration rate of the battery. In addition, the reaction of zinc-telluride batteries is a solid-solid reaction, which will cause aqueous zinc-telluride batteries to exhibit poor reaction kinetics, which is not conducive to the improvement of the electrochemical performance of aqueous zinc-telluride batteries, which further limits the development of aqueous zinc-telluride batteries. Therefore, it is very urgent to develop a method that can improve the reaction kinetics and energy density of aqueous zinc-telluride batteries. In recent years, combining metal compounds (such as manganese oxide) with conductive carbon nanomaterials to form functional composite materials can significantly enhance the reaction kinetics of the battery. In existing studies, granular manganese dioxide materials have been used to improve the reaction kinetics of the battery. For example, patent: CN 111668469 A, a positive electrode composite material and its preparation method and a lithium-sulfur battery, the method uses manganese dioxide to coat sulfur, and then uses graphene to coat the manganese dioxide / sulfur, and uses a double-layer protection structure to enhance the conductivity of the electrode material and inhibit the battery shuttle effect. However, due to the fact that manganese dioxide is coated with graphene, it cannot provide more catalytic active sites. In addition, there is a limitation that divalent manganese has poor chemical adsorption capacity and oxidation activity. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a positive electrode material of a zinc-telluride battery with hollow manganese monoxide nanospheres in view of the limitations of the current technology. The method generates a nitrogen-doped carbon nanosheet by pyrolysis of melamine, mixes the nitrogen-doped carbon nanosheet with manganese acetate tetrahydrate, and then performs a simple two-step pyrolysis reaction, thereby successfully synthesizing a manganese monoxide nanosphere with a hollow structure on the nitrogen-doped carbon nanosheet, and finally loads it with tellurium species to obtain a tellurium / manganese monoxide hollow nanosphere@nitrogen-doped carbon nanosheet heterostructure positive electrode composite material. This heterostructure can load more tellurium species. At the same time, the hollow manganese monoxide nanospheres are conducive to the penetration of electrolytes, thereby exposing more active sites. The present invention can promote the redox reaction kinetics of aqueous zinc-telluride batteries, reduce the reaction energy barrier, and thus make the aqueous zinc-telluride battery show more excellent electrochemical performance.
[0005] The technical solution of the present invention is:
[0006] A method for preparing a positive electrode material for a zinc-telluride battery with hollow manganese monoxide nanospheres, the method comprising the following steps:
[0007] (1) adding melamine and glucose into anhydrous ethanol, stirring to obtain a uniform mixed solution, and then drying to obtain a precursor;
[0008] The mass ratio of melamine to glucose is 15-25:1, the stirring time is 0.5-1.5 hours, the drying temperature is 50-70°C, and the drying time is 6-8 hours.
[0009] (2) annealing the precursor obtained in step (1) in a nitrogen atmosphere to obtain nitrogen-doped carbon nanosheets; the annealing conditions are first annealing at 400-500° C. for 1.5-2.5 hours, then heating to 750-850° C. for 0.5-1.5 hours.
[0010] (3) adding the nitrogen-doped carbon nanosheets obtained in step (2) and manganese acetate tetrahydrate into anhydrous ethanol, performing ultrasonic treatment to obtain a uniformly dispersed solution, and then performing rotary evaporation and drying to obtain a manganese acetate@nitrogen-doped carbon nanosheet mixture;
[0011] The mass ratio of nitrogen-doped carbon nanosheets to manganese acetate tetrahydrate is 1:1.8-2.1.
[0012] (4) annealing the manganese acetate@nitrogen-doped carbon nanosheet mixture obtained in step (3) under a nitrogen atmosphere, then washing it by centrifugation with water / ethanol, and then vacuum drying it to obtain a manganese monoxide solid nanosphere@nitrogen-doped carbon nanosheet heterostructure, and then annealing it again under an argon atmosphere to obtain a final product, a manganese monoxide hollow nanosphere / nitrogen-doped carbon nanosheet heterostructure;
[0013] (5) grinding and mixing the manganese monoxide hollow nanosphere@nitrogen-doped carbon nanosheet heterostructure obtained in step (4) with tellurium powder, sealing the mixture in a quartz tube, and heating the mixture to obtain a manganese monoxide hollow nanosphere zinc-tellurium battery positive electrode material;
[0014] Among them, the mass ratio of manganese monoxide hollow nanospheres@nitrogen-doped carbon nanosheets heterostructure to tellurium powder is 1:0.5-2.
[0015] In step (3), the ultrasonic time is 5 to 15 minutes, the rotary evaporation temperature is 70 to 90° C., and the rotary evaporation time is 1.5 to 2.5 hours.
[0016] In step (4), the first step annealing temperature is 250-350° C., and the annealing time is 3-6 hours; the centrifugal speed is 6000-9000 rpm, and the centrifugal time is 3-7 minutes; the vacuum drying temperature is 70-90° C., and the vacuum drying time is 5-8 hours; the second step annealing temperature is 450-550° C., and the annealing time is 3-6 hours.
[0017] In step (5), the quartz tube is heated at a temperature of 500 to 600° C. and the heating time is 10 to 15 hours.
[0018] The application of the method is used for the positive electrode of aqueous zinc-telluride batteries.
[0019] The aqueous zinc-telluride battery has a positive electrode material of the manganese monoxide hollow nanosphere zinc-telluride battery, a negative electrode of zinc foil, an electrolyte of 1M to 5M zinc trifluoromethanesulfonate, and a diaphragm of glass fiber.
[0020] The beneficial effects of the present invention are as follows:
[0021] The preparation raw material cost of the manganese monoxide hollow nanosphere @ nitrogen-doped carbon nanosheet heterostructure is low, and the preparation process is simple and easy to operate. The prepared manganese monoxide hollow nanosphere @ nitrogen-doped carbon nanosheet heterostructure can load more tellurium species and improve the utilization rate of tellurium species; the manganese monoxide hollow nanosphere is conducive to the penetration of electrolytes and can expose more active sites, which can enhance the redox reaction kinetics of aqueous zinc-telluride batteries and reduce the battery reaction energy barrier. The present invention effectively solves the problem of slow kinetics of aqueous zinc-telluride batteries. Compared with pure tellurium electrodes and nitrogen-doped carbon nanosheet-loaded tellurium species electrodes, the tellurium / manganese monoxide hollow nanosphere @ nitrogen-doped carbon nanosheet heterostructure positive electrode material exhibits the lowest reaction energy barrier. In addition, the tellurium / manganese monoxide hollow nanosphere @ nitrogen-doped carbon nanosheet heterostructure positive electrode material exhibits 427mAh g –1 The discharge capacity of pure tellurium electrode and tellurium / nitrogen doped carbon nanosheet electrode is only 163 mAh g –1 and 130mAh g –1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a scanning electron microscope image of the manganese monoxide hollow nanosphere@nitrogen-doped carbon nanosheet heterostructure prepared in Example 1.
[0023] Figure 2 This is a transmission electron microscopy image of the manganese monoxide hollow nanosphere@nitrogen-doped carbon nanosheet heterostructure prepared in Example 1.
[0024] Figure 3This is a high-magnification transmission electron microscopy image of the manganese monoxide hollow nanosphere@nitrogen-doped carbon nanosheet heterostructure prepared in Example 1.
[0025] Figure 4 This is the X-ray diffraction pattern of the manganese monoxide hollow nanospheres@nitrogen-doped carbon nanosheets heterostructure prepared in Example 1.
[0026] Figure 5 This is the Raman image of the manganese monoxide hollow nanospheres@nitrogen-doped carbon nanosheets heterostructure prepared in Example 1.
[0027] Figure 6 Preparation of tellurium / manganese monoxide hollow nanospheres@nitrogen-doped carbon nanosheet heterostructures as positive electrode materials for aqueous zinc-telluride batteries at 0.1 A g -1 Charge and discharge curves under current density.
[0028] Figure 7 The tellurium / manganese monoxide hollow nanospheres@nitrogen-doped carbon nanosheets heterostructure prepared in Example 2 was used as the positive electrode of aqueous zinc-telluride batteries at 3A g -1 Cycling stability plot at different current densities. DETAILED DESCRIPTION
[0029] The specific implementation steps and drawings of the present invention are described in full and clearly below. It is necessary to point out that the specific implementation of the present invention cannot be limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, other embodiments or inferences obtained without making innovative ideas should be considered to belong to the protection scope of the present invention.
[0030] Example 1
[0031] The specific preparation method of the manganese monoxide hollow nanosphere / nitrogen-doped carbon nanosheet heterostructure is as follows:
[0032] (1) 6 g of melamine and 300 mg of glucose were added to 20 mL of anhydrous ethanol, stirred for 1 hour to obtain a uniform dispersion, and then dried at 60° C. for 6 hours to obtain a precursor;
[0033] (2) annealing the precursor obtained above at 450° C. for 2 hours in a nitrogen atmosphere, and then heating the temperature to 800° C. at a heating rate of 2° C. / min and maintaining the annealing for 1 hour to obtain nitrogen-doped carbon nanosheets;
[0034] (3) 100 mg of nitrogen-doped carbon nanosheets and 192 mg of manganese acetate tetrahydrate were added to 10 mL of anhydrous ethanol, ultrasonically dispersed for 10 minutes, and then dried by rotary evaporation at 80°C for 2 hours;
[0035] (4) The mixture was annealed at 300°C for 5 hours in a nitrogen atmosphere, and then cooled to room temperature. The product was then centrifuged and washed with a water / ethanol mixture with a volume ratio of 1:1 at a speed of 8000 rpm for 5 minutes, and then vacuum dried at 80°C for 6 hours. The dried product was then annealed at 500°C for 5 hours in a nitrogen atmosphere, and then cooled to room temperature to obtain the final product, manganese monoxide hollow nanospheres @ nitrogen-doped carbon nanosheets heterostructure.
[0036] The final product, manganese monoxide hollow nanospheres@nitrogen-doped carbon nanosheets heterostructure, was characterized by scanning electron microscopy and transmission electron microscopy. Figure 1 As shown in the scanning electron microscopy, the manganese monoxide nanospheres are evenly distributed on the nitrogen-doped carbon nanosheets. Figure 2 As shown by transmission electron microscopy, manganese monoxide nanospheres with a diameter of 40-60 nm are uniformly dispersed on the nitrogen-doped carbon nanosheets. Figure 3 As shown by high-magnification transmission microscopy, the manganese monoxide nanospheres exhibit an obvious hollow structure.
[0037] X-ray diffraction spectra were used to analyze the heterostructure of manganese monoxide hollow nanospheres@nitrogen-doped carbon nanosheets. Figure 4 As shown in the figure, both nitrogen-doped carbon nanosheets and manganese monoxide hollow nanospheres @ nitrogen-doped carbon nanosheets heterostructures exhibit the typical (002) characteristic peak of carbon at around 25°. The three characteristic peaks exhibited by the manganese monoxide hollow nanospheres @ nitrogen-doped carbon nanosheets heterostructure at 35.1°, 40.9°, and 58.9° are the (111), (200), and (220) crystal planes of manganese monoxide. This result confirms that the manganese monoxide hollow nanospheres @ nitrogen-doped carbon nanosheets heterostructure was successfully prepared.
[0038] Raman spectroscopy was used to analyze the heterostructure of hollow manganese monoxide nanospheres@nitrogen-doped carbon nanosheets. Figure 5 As shown, the heterostructure of nitrogen-doped carbon nanosheets and manganese monoxide hollow nanospheres@nitrogen-doped carbon nanosheets is at 1356 cm -1 and 1579cm -1 The typical D band and G band characteristic peaks of carbon are shown on both sides. The MnO hollow nanospheres@nitrogen-doped carbon nanosheet heterostructure is at 649 cm -1 The results show that the Mn-O vibration band is extra. This result confirms the successful preparation of the MnO hollow nanospheres@nitrogen-doped carbon nanosheets heterostructure.
[0039] Example 2
[0040] The specific preparation method of the tellurium / manganese monoxide hollow nanosphere@nitrogen-doped carbon nanosheet heterostructure as the positive electrode material of aqueous zinc-tellurium battery is as follows:
[0041] (1) The prepared manganese monoxide hollow nanosphere@nitrogen-doped carbon nanosheet heterostructure and tellurium powder were ground in a mortar at a mass ratio of 1:1 for 20 minutes to mix them evenly and sealed in a quartz tube. The quartz tube was then heated at 550°C for 12 hours and cooled to room temperature to obtain a tellurium / manganese monoxide hollow nanosphere@nitrogen-doped carbon nanosheet heterostructure composite material.
[0042] (2) Preparation and electrochemical performance test of aqueous zinc-telluride battery positive electrode material: 70% tellurium / manganese monoxide hollow nanospheres @ nitrogen-doped carbon nanosheets heterostructure composite material, 20% conductive carbon black and 10% PVDF were ground evenly in a mortar, then made into a slurry with a certain amount of NMP and coated on a titanium foil, and then vacuum dried at 80°C for 12 hours to obtain a positive electrode. A button cell was assembled with metal zinc foil as the negative electrode, glass fiber diaphragm as the diaphragm, and 3M zinc trifluoromethanesulfonate as the electrolyte. The battery was subjected to constant current charge / discharge and cycle performance tests using the Blue Electric Battery Test System. The voltage window is 0.1-1.8V.
[0043] Aqueous zinc-telluride batteries with tellurium / manganese monoxide hollow nanospheres@nitrogen-doped carbon nanosheets heterostructure as positive electrode at 0.1 A g -1 The charge / discharge curves at current density are as follows Figure 6 The tellurium / manganese monoxide hollow nanospheres@nitrogen-doped carbon nanosheets heterostructure cathode material showed a high performance of 427 mAh g –1 The discharge capacity of pure tellurium electrode and tellurium / nitrogen doped carbon nanosheet electrode is only 163 mAh g –1 and 130mAh g –1 At the same time, the tellurium / manganese monoxide hollow nanospheres@nitrogen-doped carbon nanosheets heterostructure electrode also showed the most significant reaction platform and the smallest potential hysteresis (ΔE).
[0044] Aqueous zinc-telluride batteries with tellurium / manganese monoxide hollow nanospheres@nitrogen-doped carbon nanosheets heterostructure as cathode at 3A g -1 The cycling stability curve under current density is shown in Figure 7 Aqueous zinc-telluride battery with tellurium / manganese monoxide hollow nanospheres@nitrogen-doped carbon nanosheets heterostructure as positive electrode at 3A g -1 After 2500 cycles at the same current density, the capacity retention rate is still 84.6%, while the capacity retention rate of the tellurium / nitrogen-doped carbon nanosheet positive electrode is only 59.2% after 2500 cycles, and the pure tellurium electrode can only cycle 200 cycles. This shows that the presence of manganese monoxide hollow nanospheres is beneficial to improving the electrochemical performance of aqueous zinc-telluride batteries.
[0045] Embodiment 3, Embodiment 4
[0046] The other steps are the same as those in Example 1 and Example 2, except that the mass ratio of the manganese monoxide hollow nanospheres@nitrogen-doped carbon nanosheets heterostructure to tellurium powder is replaced from 1:1 to 1:0.5 and 1:2.
[0047] The obtained material is tellurium 0.5 / MnO hollow nanospheres@nitrogen-doped carbon nanosheets heterostructures and Tellurium 2 / MnO hollow nanospheres@nitrogen-doped carbon nanosheets heterostructures.
[0048] Comparative Example 1
[0049] The other steps are the same as those in Example 1, except that the first step is annealing at 150°C and the second step is annealing at 350°C.
[0050] The obtained material is a manganese monoxide solid nanosphere@nitrogen-doped carbon nanosheet heterostructure.
[0051] Comparative Example 2
[0052] The other steps are the same as in Example 1, except that the first step is annealed for 2 hours and the second step is annealed for 2 hours.
[0053] The obtained material is a manganese monoxide solid nanosphere@nitrogen-doped carbon nanosheet heterostructure.
[0054] The reason why the hollow manganese monoxide nanospheres were not obtained in Comparative Example 1-2 was that the annealing temperature was too low or the annealing time was too short, resulting in insufficient thermal decomposition conditions for manganese acetate tetrahydrate, so that a dense manganese monoxide solid sphere structure was formed in the first annealing stage, and a hollow structure could not be formed;
[0055] Comparative Example 3
[0056] The other steps are the same as those in Example 1, except that the first step is annealing at 450°C and the second step is annealing at 650°C.
[0057] The obtained material is a shell-broken non-spherical manganese monoxide@nitrogen-doped carbon nanosheet heterostructure.
[0058] Comparative Example 4
[0059] The other steps are the same as those in Example 1, except that the first step annealing is 7 hours, and the second step annealing is 7 hours;
[0060] The obtained material is a shell-broken non-spherical manganese monoxide@nitrogen-doped carbon nanosheet heterostructure.
[0061] The reason why the hollow manganese monoxide nanospheres were not obtained in Comparative Example 3-4 was that the annealing temperature was too high or the annealing time was too long, resulting in the structure of the manganese monoxide nanospheres being too loose when formed, and thus being easily affected by the outside world when forming the hollow structure, resulting in the collapse of the structure;
[0062] Matters not covered by the present invention are known technologies.
Claims
1. A method for preparing a positive electrode material of a manganese monoxide hollow nanosphere zinc-telluride battery, characterized in that the method comprises the following steps: (1) adding melamine and glucose into anhydrous ethanol, stirring to obtain a mixed solution, and then drying to obtain a precursor; in, The mass ratio of melamine to glucose is 15-25:1, the stirring time is 0.5-1.5 hours, the drying temperature is 50-70°C, and the drying time is 6-8 hours; (2) annealing the precursor prepared in step (1) in a nitrogen atmosphere to obtain nitrogen-doped carbon nanosheets; The annealing conditions are: first at 400-500°C for 1.5-2.5 hours, then raised to 750-850°C for 0.5-1.5 hours; (3) adding the nitrogen-doped carbon nanosheets obtained in step (2) together with manganese acetate tetrahydrate into anhydrous ethanol, ultrasonically obtaining a dispersed solution, and then rotary evaporating and drying to obtain a manganese acetate@nitrogen-doped carbon nanosheet mixture; Among them, the mass ratio of nitrogen-doped carbon nanosheets to manganese acetate tetrahydrate is 1:1.8~2.1; (4) annealing the manganese acetate@nitrogen-doped carbon nanosheet mixture obtained in step (3) under a nitrogen atmosphere, then washing it by centrifugation with water / ethanol, and then vacuum drying it to obtain a manganese monoxide solid nanosphere@nitrogen-doped carbon nanosheet heterostructure, and then annealing it again under an argon atmosphere to obtain a final product, a manganese monoxide hollow nanosphere / nitrogen-doped carbon nanosheet heterostructure; (5) grinding and mixing the manganese monoxide hollow nanosphere@nitrogen-doped carbon nanosheet heterostructure prepared in step (4) with tellurium powder, sealing the mixture in a quartz tube and heating the mixture to obtain a manganese monoxide hollow nanosphere zinc-tellurium battery positive electrode material; Among them, the mass ratio of manganese monoxide hollow nanospheres@nitrogen-doped carbon nanosheets heterostructure to tellurium powder is 1:0.5~2.
2. The method for preparing the positive electrode material of zinc-tellurium battery with hollow manganese monoxide nanospheres as claimed in claim 1, characterized in that In step (3), the ultrasonic time is 5 to 15 minutes, the rotary evaporation temperature is 70 to 90° C., and the rotary evaporation time is 1.5 to 2.5 hours.
3. The method for preparing the positive electrode material of manganese monoxide hollow nanosphere zinc-telluride battery according to claim 1, characterized in that In step (4), the first step annealing temperature is 250-350°C, and the annealing time is 3-6 hours; the centrifugal speed is 6000-9000 rpm, and the centrifugal time is 3-7 minutes; the vacuum drying temperature is 70-90°C, and the vacuum drying time is 5-8 hours; the second step annealing temperature is 450-550°C, and the annealing time is 3-6 hours.
4. The method for preparing the positive electrode material of manganese monoxide hollow nanosphere zinc-telluride battery according to claim 1, characterized in that In step (5), the quartz tube is heated to a temperature of 500-600° C. and a heating time of 10-15 hours.
5. Application of the manganese monoxide hollow nanosphere zinc-telluride battery positive electrode material prepared by the method as claimed in claim 1, characterized in that it is used as the positive electrode of an aqueous zinc-telluride battery.
6. An aqueous zinc-telluride battery, characterized in that the positive electrode material of the battery is the manganese monoxide hollow nanosphere zinc-telluride battery positive electrode material prepared by the method of any one of claims 1 to 4; the negative electrode is zinc foil, the electrolyte is zinc trifluoromethanesulfonate with a concentration of 1M to 5M; and the diaphragm is a glass fiber diaphragm.
Citation Information
Patent Citations
Positive electrode composite material, preparation method thereof and lithium-sulfur battery
CN111668469A
Cited By
Aqueous tellurium battery and preparation method thereof
CN121790543A